Development of an instrument to measure the level of affective maturity of college seminarians in Panay, Negros, and Cebu. - Sarabia, Joselito S.
The researcher in this study gathered the indicators of affective maturity and tested their validity and reliability in order to construct an instrument to measure the level of affective maturity of seminarians. A total of 150 item-indicators were collected from official ecclesiastical documents relevant to seminary formation